FeCrMoWCBY metallic glass with high corrosion resistance in molten lead–bismuth eutectic alloy. (September 2021) - Wei, X.S.; Jin, J.L.; Jiang, Z.Z.; Liang, D.D.; Shen, J.
Highlights: Fe-based metallic glass exhibited excellent corrosion resistance in the oxygen-saturated LBE. The corrosion resistance of the Fe-based metallic glass could be enhanced by adding an appropriate amount of W element. The continuous amorphous diffusion barrier layer can prevent further corrosion of the metallic glass in LBE. Abstract: The FeCrMoWCBY metallic glass exhibited excellent corrosion resistance in oxygen-saturated lead-bismuth eutectic (LBE) at 500 °C. The corrosion resistance could be enhanced by adding an appropriate amount of W element, while excessive W deteriorated the corrosion resistance of the metallic glass. The surface of the Fe-based metallic glass was composed of an inner amorphous transition layer and outer FeCr2 O4 oxide nanocrystal layer. The continuous amorphous transition layer acted as a diffusion barrier layer to prevent further corrosion of the metallic glass.